Ghrelin and obestatin expression in serous ovarian tumours - Nurkalem, Cemile; Celik, Husnu; Dagli, Ferda; Gurates, Bilgin; Kavak, Burcin; Dogan, Zeynep; Aydin, Suleyman (Informa Healthcare, 2012)
Objective: To investigate ghrelin and obestatin expression in serous ovarian tumours. Materials and methods: Preparations of deparaffinized blocks obtained from the pathology archives of a total of 47 previously diagnosed cases of benign serous tumour (n=20), borderline serous tumour (n=7) and malignant serous tumour (n = 20) were subjected to immunohistochemical examination to find out ghrelin and obestatin expressions. Results: Mean ghrelin expressions decreased significantly in the benign group, relative to the malignant group (p < 0.05), while there was no significant change in mean obestatin expression. It was established that rates of preparations with moderate and severe ghrelin and obestatin expression displayed a significant increase from benign to malignant ones (p < 0.05). Conclusion:The fact that rates of preparations with severe expression correlated with an increase in malignancy suggests that ghrelin and obestatin may be effective in the malignant transformation in at least some cases.
Keywords: Ghrelin; obestatin; ovarian cancer